Análise existencial do fenômeno da consciência : adaptação fenomênica - Fusari, Lionara (2014)
This study investigates the manifestation of the phenomenon of human consciousness from the biological basis and also under the influente of sociocultural factors and existential components. In this sense, the relationship between mind and body is analyzed, presenting this phenomenon as a mental state that receives interferente from chemical reactions that occur in the human body. We also analyze how this interferes in the manifestation of this phenomenon. In addition to this aspect, it is emphasized the role that structuring and training play on the manifestation of conscious perceptual perspectives, in which they are recognized as relevant to the phenomenal adaptation. This dialectical dynamics, which takes place in between the mental events, contributes for the viability of the adaptations of perceptual perspectives, according to which human beings perceive the world and operate in it. In this work, we therefore seek to understand how the quest for survival and its maintenance, as well as the achievement of the needs raised by society and the search for knowledge, operate like demands or subjections that provide adjustments in one's conscious perceptual perspectives.